MERK SEBAGAI KEKUATAN PERUSAHAAN DALAM PERSAINGAN GLOBAL DENGAN PENDEKATAN THREE LENSES - Hariandja, Evo S. (Industrial and Systems Engineering Assessment Journal (INASEA), 2004)
Brand function as companyâs strengh in the global competition needs a different approach by reffering to the three lenses: strategic design lens, political design lens, and cultural design lens. The three lenses have component that become a key of a brand. The lader role as interest builder, supporter, and pioneer of brand component is very important thing to be notice.